Exemplary Agriculture Independent Organic Farming in Contemporary China - Cody, Sacha; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
"This book will be of great interest to everyone interested in China's recent agricultural history and the future of sustainable food production in the developing world. The author has done first-hand ethnographic research on a wide variety of topics: labor relations, commodity production, pricing, consumption, organic movements, and the ever-changing nature of state regulation. Cody's book thus constitutes a foundation for all future work in this field." -James L. Watson, Fairbank Professor of Chinese Society and Professor of Anthropology Emeritus, Harvard University "This is a timely and brilliant ethnography for the studies of foodways, and the case in Shanghai sheds light on the emergence of independent organic farming worldwide and in relation to food movements in many Asian societies in particular. -Sidney C. H. Cheung, Professor, Department of Anthropology, The Chinese University of Hong Kong This book is an important contribution to our understanding of food in China through an ethnographic case study of an alternative food movement in Shanghai and the surrounding countryside. Cody examines a group of middle-class urban residents who move to the countryside to establish small-scale and independent organic farms. The book explores the complex relationships movement protagonists have with customers in the city, rural neighbours in the countryside, volunteers on their farms, intellectuals involved in rural reconstruction initiatives as well as the organic items they produce. In doing so, Cody provides valuable insights into the urban/rural dichotomy and questions of morality in China today. This book speaks to several concerns associated with the accelerated modernization China and other Asian nations are experiencing, including food safety and class relations. It will appeal to scholars and practitioners across a range of fields including anthropology, food studies, rural development and China Studies. Sacha Cody, PhD, is a Postdoctoral Fellow at Hong Kong University of Science and Technology. An Australian, he has lived in China for 15 years. His research is published in Asian Anthropology,Gastronomica: The Journal of Critical Food Studies and The Asia Pacific Journal of Anthropology.
1. Introduction -- 2. China's Urban/Rural Dichotomy -- 3. Exemplarity -- 4. Shanghai's Independent Organic Farmers -- 5. Intellectuals -- 6. The Farm -- 7. The Volunteer -- 8. The Product -- 9. The Customer -- 10. Conclusion.
Keywords: Ethnology; Agriculture -- Economic aspects; Asia -- Politics and government; Sociocultural Anthropology; Agricultural Economics; Asian Politics